Model systems inform rare disease diagnosis, therapeutic discovery and pre-clinical efficacy. Issue 1 (13th March 2019) - Enikanolaiye, Adebola; Justice, Monica J.
Abstract: Model systems have played a large role in understanding human diseases and are instrumental in taking basic research findings to the clinic; however, for rare diseases, model systems play an even larger role. Here, we outline how model organisms are crucial for confirming causal associations, understanding functional mechanisms and developing therapies for disease. As diseases that have been studied extensively through genetics and molecular biology, cystic fibrosis and Rett syndrome are portrayed as primary examples of how genetic diagnosis, model organism development and therapies have led to improved patient health. Considering which model to use, yeast, worms, flies, fish, mice or larger animals requires a careful evaluation of experimental genetic tools and gene pathway conservation. Recent advances in genome editing will aid in confirming diagnoses and developing model systems for rare disease. Genetic or chemical screening for disease suppression may reveal functional pathway members and provide candidate entry points for developing therapies. Model organisms may also be used in drug discovery and as preclinical models as a prelude to testing treatments in patient populations. Now, model organisms will increasingly be used as platforms for understanding variation in rare disease severity and onset, thereby informing therapeutic intervention.